2021
DOI: 10.3390/ijms221810151
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Human Stem Cell Implantation in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a progressive debilitating neurodegenerative disease and the most common form of dementia in the older population. At present, there is no definitive effective treatment for AD. Therefore, researchers are now looking at stem cell therapy as a possible treatment for AD, but whether stem cells are safe and effective in humans is still not clear. In this narrative review, we discuss both preclinical studies and clinical trials on the therapeutic potential of human stem cells in AD. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 155 publications
(188 reference statements)
0
24
0
1
Order By: Relevance
“…In both organs, products of transplanted cells clearly influence inflammation and, in most of the cases, decrease damage with measurable effects. This is the case with neurodegenerative diseases such as ALS [ 168 ] or Alzheimer’s disease [ 169 ]. One of the probably most surprising observations, again seen in both the heart and the brain, is that those effects are often more pronounced in chronic than in acute phases.…”
Section: Conclusion Remarksmentioning
confidence: 99%
“…In both organs, products of transplanted cells clearly influence inflammation and, in most of the cases, decrease damage with measurable effects. This is the case with neurodegenerative diseases such as ALS [ 168 ] or Alzheimer’s disease [ 169 ]. One of the probably most surprising observations, again seen in both the heart and the brain, is that those effects are often more pronounced in chronic than in acute phases.…”
Section: Conclusion Remarksmentioning
confidence: 99%
“…Acetylcholinesterase inhibitors (AChEl) including donepezil and galantamine and memantine (N-methyl-D-aspartic acid (NMDA) receptor antagonists) can potentially treat the cognitive decline in AD [ 9 ]. It has been shown that AChEls can increase transmission of acetylcholine in the brain including the cerebral cortex via preventing acetylcholine breakdown by cholinesterase in synapses [ 10 ], whereas NMDA receptor antagonists can protect neuronal cells against excitotoxicity due to excessive activation of NMDA receptors [ 11 ]. Monoclonal antibodies such as Solanezumab and Aducanumab target aggregated Aβ peptides to remove excess Aβ plaques [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that AChEls can increase transmission of acetylcholine in the brain including the cerebral cortex via preventing acetylcholine breakdown by cholinesterase in synapses [ 10 ], whereas NMDA receptor antagonists can protect neuronal cells against excitotoxicity due to excessive activation of NMDA receptors [ 11 ]. Monoclonal antibodies such as Solanezumab and Aducanumab target aggregated Aβ peptides to remove excess Aβ plaques [ 10 , 12 ]. Several potential approaches for blocking tau hyperphosphorylation have also been developed [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is the seventh most common cause of death in the United States, and its fatality and prevalence are enhancing due to the increase in the elderly population. 1 AD is the most widespread kind of dementia and its symptoms are memory loss and cognitive impairment. It is accompanied by psychological symptoms, such as anhedonia, anxiety, nervousness, delusions, and depression.…”
Section: Introductionmentioning
confidence: 99%